Uso de amêndoas de manga no desenvolvimento de filmes e compósitos - Ribeiro, Hálisson Lucas (2024)
In response to the environmental crisis caused by the accumulation of petroleum-based plastics, it is imperative to develop biodegradable materials as viable alternatives. Starch stands out due to its biodegradability and availability, emerging as a promising candidate for the production of bioplastics. In this context, industrial by-products such as mango kernel represent a valuable source for the creation of these new materials. However, for these bioplastics to effectively compete with traditional polymers, it is crucial to enhance their properties and expand their production. In this study, we investigate the chemical modification of corn starch (CS) and starch extracted from mango kernel (MKS) through esterification with maleic anhydride using films obtained via casting. The feasibility of producing non-purified mango kernel flour (MKF) composites was evaluated using a central composite design with three variables: glycerol concentration, processing temperature, and MKF proportion. The addition of maleic anhydride, even at the lowest concentration evaluated (1%), reduced the viscosity of the starch film solutions. This change in the rheological parameters of the filmogenic solutions is due to a probable hydrolysis of the starch chains, and this effect is reflected in the performance of the materials. Chemical modification improved the films' tensile strength, modulus of elasticity, and reduced water solubility. All films exhibited a barrier property to ultraviolet light, maintaining a transparency above 95%. For the MKF and CS composites, various materials were obtained with distinct characteristics. The tensile strength varied between 0.67 and 9.53 MPa. The results obtained allowed us to identify that the evaluated parameters have a significant impact on the composites obtained. This allows for the development of models that describe the properties of tensile strength, elongation at break, modulus of elasticity, loss of soluble matter, a* and b* components of CIELAB, and UVA barrier. This work contributes to the advancement in the development of biodegradable and sustainable packaging materials, in line with global efforts to replace petroleum-derived plastics and mitigate the environmental impacts associated with the improper disposal of synthetic polymers.